Notes on musical instruments among the Fulani of Diamare (north Cameroon) - Erlmann, Veit (International Library of African Music, 1983)
The Central Sudan, enclosing the northern parts of the Cameroons and Nigeria, South-Niger and parte of Chad, has been viewed by different scholars under various aspects as one coherent area sharing certain cultural traits. Some of these are due to the impact of Islam during the past 500 years: town-culture, feudal social hierarchy, class distinctions, and literacy. Hence, this paper attempts to give a general account of the musical organology of the Fulani in North Cameroon and to contribute to the completion of ethnomusicological knowledge in this area through the presentation of new material and the basic facts of Fulani organology (names of instruments and their parts, social usage, history).
Keywords: Musical instruments; African Music; Cameroon